Body Dysmorphism and Sleep Quality among PCOS Patients: Assessing the Predictive Role of Alyxthymia - Perveen, Shagufta; Gulfam, Sharmeen; Khan, Hafsa (Annals of Human and Social Sciences, 2025)
PCOS is linked with psychosomatic issues such as apprehension, alexithymia, poor body image, and sleep problems. The current study mainly aims to examine the predictive role of alexithymia in the relationship between body dysmorphism and sleep quality and to explore the demographic differences in the study variables. The study was carried out on purposefully selected (N=300)PCOS patients from different hospitals and clinics. Along with a demographic sheet, the patients completed three instruments: the Pittsburgh Sleep Quality Index, the Appearance Anxiety Inventory, and the Perth Alexithymia Questionnaire. Results suggested that alexithymia significantly predicted the association between quality of sleep and body dysmorphism traits and body dysmorphism is significantly positively associated with alexithymia whereas inversely associated with quality of sleep. Marital and fertility-based differences were also proved. Study results will be helpful for professionals in resolving PCOS-related psychological issues. Future research should be based on a larger sample and longitudinal study design.